2021
DOI: 10.3389/fonc.2020.610681
|View full text |Cite
|
Sign up to set email alerts
|

Consecutive Hypoalbuminemia Predicts Inferior Outcome in Patients With Diffuse Large B-Cell Lymphoma

Abstract: The prognostic value of albumin changes between diagnosis and end-of-treatment (EoT) in diffuse large B-cell lymphoma (DLBCL) remains unknown. We retrospectively analyzed 574 de novo DLBCL patients treated with R-CHOP from our and two other centers. All patients were divided into a training cohort (n = 278) and validation cohort (n = 296) depending on the source of the patients. Overall survival (OS) and progression-free survival (PFS) were analyzed by the method of Kaplan–Meier and Cox proportional hazard reg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
12
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 26 publications
(31 reference statements)
1
12
0
Order By: Relevance
“…In this study, we retrospectively confirmed that hypoalbuminemia was not uncommon at diagnosis of de novo ARL and was associated with poor survival outcome attractively. A similar trend was observed in the analyses of HIV-negative DLBCL patients [ 22 , 24 ]. We also uncovered a strong relationship between hypoalbuminemia and poor ECOG PS as well as higher IPI score.…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…In this study, we retrospectively confirmed that hypoalbuminemia was not uncommon at diagnosis of de novo ARL and was associated with poor survival outcome attractively. A similar trend was observed in the analyses of HIV-negative DLBCL patients [ 22 , 24 ]. We also uncovered a strong relationship between hypoalbuminemia and poor ECOG PS as well as higher IPI score.…”
Section: Discussionsupporting
confidence: 85%
“…These associations with adverse prognostic factors translated into shorter OS for ARL patients with hypoalbuminemia. This indicated that serum albumin level may be not only a surrogate of poor nutritional, but also driven by the aggressive tumor behavior and inflammatory status [ 24 , 28 ], which was correlated with shorter survival, treatment response, treatment-related toxicity and compliance [ 22 ].…”
Section: Discussionmentioning
confidence: 99%
“… 13 , 24 , 25 , 26 , 27 Hypoalbuminaemia is a predictive factor for shorter survival, decreased relative dose intensity of anthracycline and cyclophosphamide, and increased risk of TRM. 28 , 29 , 30 , 31 , 32 High NLR is also correlated with shorter survival, lower CR rate, advanced stage, higher LDH level, and increased risk of depression. 32 , 33 , 34 , 35 , 36 , 37 The CXI comprehensively assesses these clinical parameters, and therefore may more effectively overcome the bias caused by confounding factors affecting the clinical outcomes of the patients than any single parameter of cancer cachexia.…”
Section: Discussionmentioning
confidence: 98%
“… 15 Based on the function of ALB, T‐CHOL, and TL, the associations between CONUT score and the basic variables of ENKTL might be clarified, as ALB, for an example, is used for the assessment of nutritional status as well as immune function. 28 Most cancer patients diagnosed with hypoalbuminemia were placed in the advanced stage category. When the ALB level is less than 30 g/L, the body might not be able to resist the invasion of foreign pathogens, resulting in the release of inflammatory cytokines, which might cause B symptoms.…”
Section: Discussionmentioning
confidence: 99%